"Knowledge management applications in human capital investment "Case Study on the Human Resources Sector of Saudi Air Lines Company - Sindi, Yasser Omar; Al-Surayhi, Hassan Awad (Journal of Economic, Administrative and Legal Sciences, 2017)
The study aimed to identify to clarify the role that can be played by Knowledge Management in human capital investment applications company Saudi Arabian Airlines,  furthermore the study aimed to identify the Recognize reality of Knowledge Management in the field of human capital investment applications, As well as to identify the most serious obstacles Knowledge Management applications for the investment and development of human resources, to fulfill these objectives the descriptive analytical method is used in this study, where the researcher used the questionnaire to collect primary data through direct questions and inquiries. The study population consisted of personnel management of human resources in the company reached (586) employee, and researcher selected a simple random sample of the total overall society for the study size was (296) employee of the total community individual. the study concluded that the results of the study concluded that there are many positive indicators suggest that Knowledge Management applications for human capital investment available air transport sector is very high degree, the study also pointed that there are some Knowledge Management for the investment of human capital need to activate up to fit and perform its vital role in the development of human resources of the company. the study also showed that the most important human resource management needs to support Knowledge Management applications represented in the existing knowledge of the staff need to modern techniques to be published, also through the importance of spreading knowledge and culture through seminars, workshops, training programs. The study results revealed that the technologies of Knowledge Management is very vital role in the development of investment in human capital and by providing a work environment that encourages creativity and excellence. the main recommendations of  the  study that need to maintain the current ratio of Knowledge Management, and encourage a culture of acquiring new knowledge and information among workers, and need that the administration working to provide advanced systems for service personnel, and the need for attention to the deployment of knowledge and culture through seminars, workshops, training programs and need to focus on knowledge management techniques as they have a very vital role in the development of investment in human capital through the dissemination of information and disseminating them among employees where this will contribute to make them aware of, and that the administration need to working to open the channels of effective communication between them and the staff through the activation of all media and means of communication between them. And the need to provide a working environment that encourages creativity and excellence, the researcher recommended further studies on the subject as there is scarcity in such studies in the local environment of the Kingdom of Saudi Arabia.
Keywords: Saudi Arabian Airlines air transport company; knowledge; management; human resources; human capital